Efektivitas Jaminan, Relevansi, Minat, Penilaian, Model And Satisfaction (ARIAS) Terhadap Self-Efficacy Siswa Pencapaian - Novalina Indriyani; Yanti Fitria; Darmansyah; Melva Zainil (Postgraduate, University of Mataram, 2023)
This study was motivated by the low self-efficacy of students in IPAS learning. This study aims to determine the effectiveness of the Assurance, Relevance, Interest, Assessment, and Satisfaction (ARIAS) model on the achievement of self efficacy in grade IV elementary school. The type of research used is Quasi Experimental using Nonequivalent Control Group Design. The study population was grade IV elementary school students in Gugus VI Koto Tangah District, Padang. The sampling technique used was Simple Random Sampling, obtained class IVA as the experimental class and class IVB as the control class at SD Negeri 28 Padang Sarai. This research instrument is a self efficacy questionnaire and data analysis techniques using prerequisite tests in the form of normality, homogeneity, and independent sample t test tests. Based on the results of the study obtained a significance value of Sig. 0.00 < 0.05, that H0 is rejected and H1 is accepted, which means that the effectiveness of the ARIAS model has a significant effect on the achievement of self efficacy of students in elementary schools. Learning with the ARIAS model makes students active in learning activities.